Effects of Lemmon Grass (Cymbopogon citratus) Leaf Meal Feed Supplement on Growth Performance of Broiler Chicks - Mmereole, F.U.C. (International Journal of Poultry Science, 2010)
An experiment was conducted to evaluate the effects of dietary inclusion of Lemmon Grass (Cymbopogon citratus) Leaf Meal (LGLM) on growth performances of broiler chickens and its ability to be utilized as a viable alternative to antibiotic growth promoters. The experiment involved two hundred and seventy day-old Abor-acre broiler chickens randomly separated into 3 experimental diet groups, with each being replicated 3 times. Ninety day-old birds were randomly allocated to each group and thirty birds per replicate. The diet groups were: Diet 1 (D 1 = control = basal diet), Diet 2 (D 2 = basal diet +1% LGLM) and Diet 3 (D 3 = basal diet+1% Teramycin antibiotic growth promoter). The birds were brood-reared for six weeks. At day-old the birds were weighed to obtain the initial weight and subsequently weighed weekly to determine weekly body weights and weekly body weight gains. Other parameters taken weekly included feed intake, feed conversion ratio and mortality rates. All the parameters were subjected to statistical analysis using SPSS 2006. The results obtained indicate that the performances of the birds placed on control diet (D1) were significantly (p<0.05) lower in all parameters than those placed on D2 and D3. The results further indicated that, although the final body weight of the birds on D2 (1895.56 g) was quantitatively higher than that of the birds in D3 (1875.92 g), the difference was not significant (p>0.05). With respect to feed intake and feed conversion ratio, it was observed that there were no significant differences between the birds in D2 and D3. At the end of the experiment the cumulative mortality rate in D2 (3.67%) was found to be significantly (p<0.05) lower than the mortality rate for the birds in D3 (3.98%). Based on these results, it can be concluded that, considering the risk of drug resistance which the antibiotics tend to impose on broilers, Lemmon grass leaf meal can be considered as a viable alternative to antibiotics growth promoters.